The components of the illiquidity premium: An empirical analysis of U.S. stocks 1927-2010 - Björn Hagströmer; Birger Nilsson; Björn Hansson (Lund University, School of Economics and Management, Department of Economics, 2011)
This paper estimates a conditional version of the liquidity adjusted CAPM by Acharya and Pedersen (2005) using NYSE and AMEX data from 1927 to 2010 to study the illiquidity premium and its variation over time. The components of the illiquidity premium is in this model derived as the level of expected illiquidity together with three types of illiquidity risks. We measure illiquidity of individual stocks by the efficient spread proxy developed in Holden (2009) and employ illiquidity sorted portfolios as test assets. The average annual illiquidity premium is estimated to 1.55%, the respective contributions from illiquidity level being 1.15% and from the three different illiquidity risks 0.40%. Results also indicate that commonality risk is the least important component in the illiquidity risk premium, while a component related to the hedging of wealth shocks is the most important. The illiquidity premium varies substantially over time, with peaks in downturns and crises, but with no general tendency to decrease over time.
Keywords: C22; G11; G12; 330; illiquidity level premium; illiquidity risk premium; conditional LCAPM; effective tick